Worker health chartbook 2004 - USA. National Institute for Occupational Safety and Health (Cincinnati, 2004)
"The Chartbook is a descriptive epidemiologic reference on occupational morbidity and mortality in the United States. A resource for agencies, organizations, employers, researchers, workers, and others who need to know about occupational injuries and illnesses, the Chartbook includes more than 400 figures and tables describing the magnitude, distribution, and trends of the Nation’s occupational injuries, illnesses, and fatalities."